Tissue-Engineered Vascular Graft of Small Diameter Based on Electrospun Polylactide Microfibers - Popryadukhin, P. V.; Popov, G. I.; Yukina, G. Yu.; Dobrovolskaya, I. P.; Ivan’kova, E. M.; Vavilov, V. N.; Yudin, V. E. (International Journal of Biomaterials, 2017)
Tubular vascular grafts 1.1 mm in diameter based on poly(L-lactide) microfibers were obtained by electrospinning. X-ray diffraction and scanning electron microscopy data demonstrated that the samples treated at T=70°C for 1 h in the fixed state on a cylindrical mandrel possessed dense fibrous structure; their degree of crystallinity was approximately 44%. Strength and deformation stability of these samples were higher than those of the native blood vessels; thus, it was possible to use them in tissue engineering as bioresorbable vascular grafts. The experiments on including implantation into rat abdominal aorta demonstrated that the obtained vascular grafts did not cause pathological reactions in the rats; in four weeks, inner side of the grafts became completely covered with endothelial cells, and fibroblasts grew throughout the wall. After exposure for 12 weeks, resorption of PLLA fibers started, and this process was completed in 64 weeks. Resorbed synthetic fibers were replaced by collagen and fibroblasts. At that time, the blood vessel was formed; its neointima and neoadventitia were close to those of the native vessel in structure and composition.